2009
DOI: 10.1111/j.1399-3054.2008.01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the secretome of rice calli

Abstract: The cell wall and extracellular matrix in higher plants include secreted proteins that play critical roles in a wide range of cellular processes, such as structural integrity and biogenesis. Compared with the intensive cell wall proteomic studies in Arabidopsis, the list of cell wall proteins identified in monocot species is lacking. Therefore, we conducted a large-scale proteomic analysis of secreted proteins from rice. Highly purified secreted rice proteins were obtained from the medium of a suspension of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 48 publications
3
65
0
2
Order By: Relevance
“…Quantitative proteomics techniques such as stable isotope labeling by amino acids in cell culture (SILAC) have been refined to suit plant systems and exploited recently in Arabidopsis suspension cell culture systems to analyze relative protein expression levels (Gruhler et al 2005;Schütz et al 2011). High-throughput transcriptomic (Singla et al 2007;Bao et al 2009) and proteomic techniques (Yin et al 2007;Marsoni et al 2008), state-of-the-art protein analysis techniques such as liquid chromatography mass spectrometry (LC-MS) (Jung et al 2008) and multidimensional protein identification technology (MudPIT) (Chen et al 2009b;Cho et al 2009) are extremely powerful tools to simultaneously identify and monitor a large number of RNA/protein and their expression changes in vitro. Some of the techniques used for analyzing the variations generated under in vitro culture conditions are summarized in Table 1.…”
Section: Gene Expression Regulation Of Developmental Cell Fate In Vitromentioning
confidence: 99%
“…Quantitative proteomics techniques such as stable isotope labeling by amino acids in cell culture (SILAC) have been refined to suit plant systems and exploited recently in Arabidopsis suspension cell culture systems to analyze relative protein expression levels (Gruhler et al 2005;Schütz et al 2011). High-throughput transcriptomic (Singla et al 2007;Bao et al 2009) and proteomic techniques (Yin et al 2007;Marsoni et al 2008), state-of-the-art protein analysis techniques such as liquid chromatography mass spectrometry (LC-MS) (Jung et al 2008) and multidimensional protein identification technology (MudPIT) (Chen et al 2009b;Cho et al 2009) are extremely powerful tools to simultaneously identify and monitor a large number of RNA/protein and their expression changes in vitro. Some of the techniques used for analyzing the variations generated under in vitro culture conditions are summarized in Table 1.…”
Section: Gene Expression Regulation Of Developmental Cell Fate In Vitromentioning
confidence: 99%
“…Furthermore, when secreted proteins of rice were compared in planta and in vitro, the ratios of signalpeptide-containing proteins were 77% and 27%, respectively (Jung et al, 2008), indicating the importance of in planta experiments in investigating the roles of secreted proteins in nature. Cho et al (2009) found that only 27.7% of the identified proteins were secreted proteins from rice calli, and they reported that the possibility of contamination and/or the prediction of the signal peptide were not sufficient.…”
Section: Proteome Analysis On Proteins Secreted Into the Rhizospherementioning
confidence: 97%
“…Proteome analyses of several plant body components and intracellular structures have been successful. Reports have been accumulating on the rice proteome of phloem and xylem sap (Aki, Shigyo, Nakano, Yoneyama, & Yanagisawa, 2008), the plasma membrane (Natera et al, 2008) and the vacuolar membrane (Whiteman, Nühse, Ashford, Sanders, & Maathuis, 2008), the secretome in relation to the cell wall (Cho et al, 2009), the etioplast (von Zychlinski et al, 2005 and other plastids (Kleffmann et al, 2007) and some other organelles (Tanaka et al, 2004). Technical development in purification of sub-cellular and suborganellar structures and in protein preparation, such as selective removal of high-abundance proteins, helps with in-depth research on low-abundance proteins (Li, Nallamilli, Tan, & Peng, 2008).…”
Section: Ricementioning
confidence: 99%